2021
DOI: 10.3390/pharmaceutics13091451
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alkanediols on Stratum Corneum Lipids and Triamcinolone Acetonide Skin Penetration

Abstract: Alkanediols are widely used as multifunctional ingredients in dermal formulations. In addition to their preservative effect, considering their possible impact on drug penetration is also essential for their use. In the present study, the influence of 2-methyl-2,4-pentanediol, 1,2-pentanediol, 1,2-hexanediol and 1,2-octanediol on the skin penetration of triamcinolone acetonide from four different semisolid formulations was investigated. Furthermore, confocal Raman spectroscopy measurements were performed to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Recent studies showed that diols, including 1,2-pentanediol, are taken up into SC. It is hypothesized that the hydrophilic regions in the SC might be increased after taking up 1,2-pentanediol and caffeine can thus be deposited in these regions more easily [23]. This can explain the penetration profile of caffeine from the solution containing 1,2-pentanediol obtained by tape stripping, since the lower layer of the stratum corneum, the stratum conjunctum, is more hydrophilic than its upper layer, the stratum disjunctum, as it contains a higher amount of polar lipids [24,25].…”
Section: Tape Stripping Resultsmentioning
confidence: 99%
“…Recent studies showed that diols, including 1,2-pentanediol, are taken up into SC. It is hypothesized that the hydrophilic regions in the SC might be increased after taking up 1,2-pentanediol and caffeine can thus be deposited in these regions more easily [23]. This can explain the penetration profile of caffeine from the solution containing 1,2-pentanediol obtained by tape stripping, since the lower layer of the stratum corneum, the stratum conjunctum, is more hydrophilic than its upper layer, the stratum disjunctum, as it contains a higher amount of polar lipids [24,25].…”
Section: Tape Stripping Resultsmentioning
confidence: 99%
“…Thus, vitamin E could be additional protection from the dehydration and degradation that occurs throughout the imaging process. Preservative, caprylyl glycol is a surfactant that can disrupt membranes [ 34 , 47 ]. In our study, treatment with BZK + caprylyl glycol had epidermal thicknesses similar to skin treated with just water.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these excipients in cosmetic solutions are used as preservatives, emulsion agents, and antioxidants [ 33 ]. Previous studies have shown that caprylyl glycol [ 34 ] and vitamin E [ 35 , 36 ] can influence the penetration of drugs. Two commercial solutions which contain a mixture of several excipients were also analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…52,54,106,107,108,109 Rodent skin 110 is rarely due to its inherent differences to human skin. Caffeine, 52,106,109,111,112,113 lidocaine, 104 procaine, 107,114 tetracaine, 115 salicylic acid, 113 ibuprofen, 103 flufenamic acid, 105 imiquimod, 116 trans-retinol, 117,118 resorcinol, 75 niacinamide, 119 sulfathiazole sodium, 54 triamcinolone acetonide 120 and oxaprozin are among the most investigated permeants in the CRS penetration studies. 99 Next to these drugs, the penetration of enhancers such as DMSO, 54,121 propylene glycol, 103,106,107,118 polyoxyethylene-23-lauryl ether 107 and other ethoxylated emulsifier systems 114,122 has been evaluated.…”
Section: Skin Penetration Studiesmentioning
confidence: 99%
“…TA B L E 1 Assignment of spectral bands in healthy human skin after 35 The skin penetration of classic anionic surfactants such as sodium dodecyl sulphate (SDS) or sSLES has likewise been investigated in numerous studies, often as positive control. 54,123,124 Regarding skin penetration of additives used in cosmetic or pharmaceutical preparations, data on the penetration behaviour of oils or waxes, 95 preservatives 120 or sunscreen agents 125 have been presented.…”
Section: Skin Penetration Studiesmentioning
confidence: 99%